Urban hopes : made in China by Steven Holl - Kumpusch, Christoph a. (Lars Müller, 2014)
In content and format the book reflects such juxtaposition, featuring images and graphic documentation of Steven Holl's recent works realized in China alongside critiques and analyses by a new generation of theorists.